2018
DOI: 10.3390/nu10060735
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effects of Insect Extracts in an Animal Model of Nonalcoholic Fatty Liver Disease

Abstract: Insects represent the largest and most diverse group of organisms on earth and are potential food and drug resources. Recently, we have demonstrated that a Forsythia viridissima extract prevented free fatty acid-induced lipid accumulation in an in vitro cellular nonalcoholic fatty liver disease (NAFLD) model. In this study, we aimed to evaluate the hepatoprotective effects of extracts of the insects Protaetia brevitarsis seulensis Kolbe, 1886 (PB), Oxya chinensis sinuosa Mishchenko, 1951 (OC), and Gryllus bima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 39 publications
(36 reference statements)
0
30
0
Order By: Relevance
“…As mentioned above, the high-fat diet directly caused lipid metabolism disorder, and simultaneously lead to the imbalance of lipids synthesis and catabolism in the liver. And mild NAFLD was formatted accompany with excessive hepatic lipids accumulation as a result of higher calories food 12 . Similar results were observed by liver pathology changes in this study Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, the high-fat diet directly caused lipid metabolism disorder, and simultaneously lead to the imbalance of lipids synthesis and catabolism in the liver. And mild NAFLD was formatted accompany with excessive hepatic lipids accumulation as a result of higher calories food 12 . Similar results were observed by liver pathology changes in this study Fig.…”
Section: Discussionmentioning
confidence: 99%
“…What s more, literature reported that the over-expressed of lipogenic genes such as SREBP-1c, PPARγ, FAS and so on in the liver increased the risk of inflammation and hepatic steatosis 21 . SREBP-1c is regarded as a critical transcription factor for TG synthesis 35 , which could decrease the expression of lipogenic enzymes, including FAS, ACC, and SCD1 12,24 . PPARγ, which regarded as an important transcription factor in adipogenesis 36 , involving in the micro vesicular accumulation of lipids droplets and glucose homeostasis 38 , and its downstream gene mainly contained FAS, AP2, and LPL.…”
Section: Discussionmentioning
confidence: 99%
“…All data presented herein were obtained from refs. [44,54,55,70,72,74,75,78,88,95,96,98,102–111,116,119–121,124–130,132,134–137,140–144,147–156,158,159,161,163–171,173–176...…”
Section: Diet Composition and Exposure Timementioning
confidence: 99%
“…All data presented herein were obtained from refs. [70,72,74,77,78,88,95,96,98,104,105,107,109–112,114–128,130,132,133,135–142,144–146,148,150,151,153,154,157,159,161–168,174,176–184,187,188,190,191,194,196–198,200–204,206,208–212,215,217,219–226,229,230,232–235,237,239–242,244,250–253,257,258,263,264,266–268,270–276,278,285,287–290,292,295,296,298–301,303,304,308–310,314,316,317,319,321,322,324,325,329,331–342].…”
Section: Diet Composition and Exposure Timementioning
confidence: 99%
“…Many recent results provide evidences that effects of edible insect extracts against liver diseases (Ahn et al, 2014;Im et al, 2017;Kim and Chae, 2018;Lee et al, 2017a;Lee et al, 2017b). Our results also provide an insight to the development of KLF4-related disease therapies through gene expression regulation of KLF4 using A. dichotoma hemolymph combined with mild ER stress (Yoshida & Hayashi, 2014;Lu et al, 2015).…”
Section: Brief Communicationmentioning
confidence: 99%